(untitled) (Fiep Bulletin - online, 2011)
The promotion of a more active life in old age has been used as a strategy to promote improvement in health standards and quality of life. The aim of this study was to diagnose the number of obese women by anthropometric measures, residents in the city of Partridges - Minas Gerais. The sample consisted of 75 women, 60 to 86 years of age, thus constituting 20% of the resident population as of August 2006 Perdizes - Minas Gerais. Were assessed for body mass index - BMI (P / M ²), waist and hip circumference - WHR (C / Q), skinfold thickness triceps, suprailiac and abdominal - DOC. For the classification of obesity, we used the BMI criteria Linschitz (1994) adopted by the Ministry of Health through the SISVAN. The ratings of WHR (waist / hip ratio) were diagnosed according to (Gray, Bray, 1988 apud MARINS; Giannichi, 2003, p.74). The amount of fat was estimated by the predictive model proposed by Jackson, Pollock (1985) and Siri (1961). With respect to BMI, 52% of the volunteers showed obesity, 33.3% were normal / healthy weight and 14.7% with low weight. The prevalence of inadequate waist-hip ratio was 70.7% of volunteers surveyed found themselves in rank very high, the WHR. About 38.7% of the volunteers studied had become obese by using skinfold method - DOC. We conclude that the elderly women of the city of Partridges have a tendency to develop a framework for obesity. Obesity is a significant health problem. Exercise is an important predictor of success for weight reduction, which is why a greater physical activity is a key goal for those wishing to lose weight.